Time-Dependent Mass Transport for O2 Reduction at the Pt | Perfluorosulfonic Acid Ionomer Interface. (1st November 2014) - Novitski, David; Xie, Zhong; Holdcroft, Steven
Abstract : Chronoamperometric analysis of the oxygen reduction reaction (ORR) at Pt microelectrode | perfluorosulfonic acid (PFSA) ionomer interfaces in a solid state electrochemical cell reveals an increase in both the oxygen diffusion coefficient (Db ) and oxygen permeability (Db cb ) upon consecutive potential step measurements. From a vapor-equilibrated, electrochemically unperturbed state under conditions of 70% RH and 50°C, Db and Db cb increased by factors of 2 and 1.5, respectively. Db and Db cb return to their initial values after resting the electrode at the open circuit potential. The electrochemical generation of water is believed responsible for the time-dependent mass transport parameters of ORR.